Avaliação de seis variedades de uvas sem sementes no Submédio São Francisco - Leão, Patrícia Coelho de Souza; Pereira, Fernando Mendes [UNESP] (FapUNIFESP (SciELO), 2001)
This work aimed to study aspects related to vegetative and productive development of plants and characteristics and chemical components of bunches of six seedless grape varieties at environmental conditions of São Francisco river's valley, Northeastern Brazil. The experiment was carried out during 1997 and 1998. The varieties tested were grafted on IAC 572 ('Jales') rootstock. The experimental model utilized was totally randomized, and with parcels subdivided into different production cycles. The results showed significative differences among varieties at different pruning times. The average weight of bunches varied from 164.8 g for 'Marroo Seedless' and 203.5 g for 'Beauty Seedless'. The average diameter of berries was superior to 15.7 mm for all of the varieties. The total soluble solids varied from 14.05°Brix in 'Canner' to 19.6°Brix in 'Venus'. The total titratable acidity (ATT) was lower than 0.91 g tartaric acid/100 mL of juice. The ratio SST/ATT varied from 19.05 in 'Beauty Seedless' to 28.57 in 'Vênus'. 'Vênus' and 'Marroo Seedless' were the most productive varieties, with the average annual production of 24 ton/ha and 20 ton/ha, respectively.

Este trabalho teve como objetivo avaliar aspectos relacionados ao desenvolvimento vegetativo e produtivo das plantas, às características físicas e à composição química dos frutos de seis variedades de uvas sem sementes nas condições do Submédio São Francisco. Os dados foram registrados durante os anos de 1997 e 1998. As variedades utilizadas foram enxertadas sobre o porta-enxerto IAC 572 (`Jales'). O delineamento experimental foi inteiramente casualizado, com parcelas subdivididas nos ciclos de produção. Houve diferenças significativas na resposta da maioria das variedades entre as épocas de poda. O peso médio dos cachos variou entre 164,8 g na variedade Marroo Seedless, e 203,5 g na `Beauty Seedless'. O diâmetro médio das bagas foi superior a 15,7 mm em todas as variedades. Foram obtidos teores de sólidos solúveis compreendidos entre 14,05ºBrix na variedade Canner e 19,6ºBrix na `Vênus', enquanto a acidez total titulável foi inferior a 0,91 g de ácido tartárico/100 mL de suco, resultando em adequadas relações SST/ATT, que variaram entre 19,05 na variedade Beauty Seedless a 28,57 na `Vênus'. As variedades Vênus e Marroo Seedless foram as mais produtivas, com produtividades anuais de 24 t/ha e 20 t/ha, respectivamente.
Evaluation of six seedless grape varieties under the conditions of São Francisco river's valley
Keywords: Fruits; Grapevines; Plant developmental stages; Vitis vinifera; Yield